Investigation of plasma vitamin D, vitamin B12, and folate levels in newborns with pathological jaundice without risk factors - Fatih Kurt; Fatih Davran; Abdulkadir Kaya; Kenan Kocabay (Egyptian Pediatric Association Gazette)
Abstract Background Physiological jaundice of the newborn is usually benign condition. Hyperbilirubinemia occurs as a result of postnatal breakdown of hemoglobin F and functional failure of the neonatal liver. Neonatal physiologic jaundice is seen in approximately two-thirds of term infants. Fifteen percent of neonatal jaundice reaches the pathological level. The etiology of nearly half of the cases is unknown. Considering the prevalence of pathological jaundice and its neurological side effects, it is very important to elucidate the etiology. This study was designed to investigate the potential role of vitamin B12, folate, and 25-OH vitamin D in the etiology of neonatal jaundice, considering their effects on erythrocyte maturation and cell lysis through various mechanisms. Methods A patient group was formed from 40 newborns and their mothers who developed pathological jaundice despite the absence of known risk factors. The control group consisted of 36 infants and their mothers who did not develop pathological jaundice. Demographic characteristics (age, gender, etc.), laboratory findings, plasma 25(OH) vitamin D, vitamin B12, and folate level results of both groups were compared. Results Newborn plasma vitamin B12 and especially plasma folate levels were significantly lower in the patient group (p 0.048, < 0.001, respectively). There was no significant difference in 25(OH) vitamin D levels in both groups. A positive correlation was found between the vitamin levels of mothers and babies. Conclusion Our study suggests that lower neonatal folate and vitamin B12 levels, along with higher maternal 25(OH) vitamin D levels, may be associated with pathological jaundice.